A contribuição de diversos segmentos corporais na execução do teste sentar e alcançar - Perin, Andrea (2013)
The Sit and Reach Test (SR) is the most widely used assessment of hamstrings flexibility, however, some factors can influence their results as a behavior of the spine. This research aims to determine the contribution of the hip joint, of the lumbar and thoracic spine in the execution of SR in young Brazilians. The descriptive observational study subjects were 195 young men from 18 to 19 years. To identify the contribution of body segments in flexion of the trunk it was evaluated the SR together with angular kinematic analysis through of Photogrammetry. To that end, we developed a protocol for evaluating reference angles that were transformed into percentage contribution of the segments. The angles and percentages were classified into two reference standards of the SR, which identified that the best ranking in SR, greater use of hip and lower utilization of the thoracic spine. The lumbar spine was stable during movement. The angles and percentages were also classified in the categories of BMI, revealing that obese people use more hip to perform the movement, because they cannot make compensation with thoracic spine. Based on the results, it was possible to create a table of classification of angles and percentages, which allowed for the identification and compensation movement patterns in accordance with the condition of the muscles involved. It can be concluded the contributions of the thoracic spine, lumbar spine and hip in performing the SR are respectively 46.014%, 12.676%, 41.309%. However, only the measure of the SR does not permit this detail because its result refers to the total trunk flexion and hip flexion. Thus, it is recommended that evaluation of flexion of the thoracic spine, lumbar spine and hip joint are performed separately by photogrammetry, based on the average parameters and protocol established in this study, through the classification of their values in the proposed categories.